The Effect of Sustainable Agricultural Practices, Product Diversification, and Digital Marketing on the Economic Performance of Organic Vegetable Farmers in Bali - Sudirjo, Frans; Lestari, Mufida Diah; Haryono, Haryono; Faisal, Herry Nur; Sajali, Chusnatul Ulaela (Westscience Press, 2024)
This study examines the impact of sustainable agricultural practices, product diversification, and digital marketing on the economic performance of organic vegetable farmers in Bali. Employing a quantitative approach, data were collected from 210 farmers using a structured questionnaire with a 5-point Likert scale. The analysis was conducted using Structural Equation Modeling with Partial Least Squares (SEM-PLS). The results reveal that product diversification has the strongest positive influence on economic performance, followed by sustainable agricultural practices and digital marketing. Product diversification enhances income stability and market expansion, while sustainable practices improve cost efficiency and product quality. Digital marketing, although less impactful, provides significant benefits by increasing market reach and customer engagement. These findings highlight the synergistic effects of these strategies in improving the economic resilience of organic farmers. The study concludes with actionable recommendations for farmers, policymakers, and stakeholders to foster sustainable and profitable organic farming.